Analysis of the Quantitative Strategic Planning Matrix in the Management of Legomoro Twin Waterfall Tourist Attraction in Banyuwangi Regency - Ninik Wahyu Indartik; I Putu Anom; I Nyoman Sukma Arida (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to identify the existing conditions of the tourist attraction of the Legomoro Twin Waterfall and propose a management strategy. The Legomoro Twin Waterfall was chosen because many people are involved in the management. The approach used is qualitative descriptive and supported by quantitative data, data sources are obtained through observation, interviews, documentation, literature studies and questionnaires. Data analysis was carried out using IFE and EFE, IE matrix, SWOT matrix and QSPM. The results of the study show that the tourist attraction of Legomoro Twin Waterfall has great potential in the components (4A) of attraction, accessibility, amenities, and ancillary for the development of agro-tourism and is supported by internal and external factors. IE matrix analysis puts the management of the Legomoro Twin Falls in a hold and maintain position, with a focus on market penetration and product development. The SWOT analysis resulted in seven alternative strategies: (SO) Utilizing the potential of Legomoro Waterfall to sell many tour packages online and attractively designed and improving the quality of facilities and infrastructure of Legomoro Waterfall, (WO) Improving the quality of human resources of industry players in Legomoro Waterfall by conducting counseling to the local community, (ST) Exploring the potential and strengthening the authenticity of nature, historical values and traditions and culture of the local community as an attraction of Legomoro Waterfall and Improving disaster mitigation in tourist attractions, (WT) Paying attention to the quality and quality of service to tourists and Increasing awareness and discipline to the community. QSPM analysis shows that increasing awareness and discipline to the community is a top priority with a TAS value of 8.00 for the management of the Legomoro Twin Waterfall tourist attraction.